Documentário queer no Sul do Brasil (2000 a 2014): narrativas contrassexuais e contradisciplinares nas representações das personagens LGBT - Pereira, Dieison Marconi (2015)
Through a queer perspective, this study aims to investigate the representations of LGBT characters in documentaries produced in southern Brazil between 2000 and 2014. By understanding sexuality as a historical device regulation and social order, we discussed how these films appear the representations of gender, body and sexuality of "abject subject" and how to take or not a counteraesthetics and resistance to sexed and gendered norms. Representations as anchors narratives contribute to understanding the processes of imagining and recognize each other, because every film produces representations submitted to the view of a self enunciator, that is, as others see us and design in the film portraits. Postulate that horizon, the intention of this work unfolds in: (1) investigate the ethical stances of the works to articulate the film universe, leading the meanings given to LGBT characters; (2) analyze how the technical and stylistic devices used in the documentary contribute or not to the subversions of discriminatory film portraits; and (3) understand what are the representations that this movie has figured to establish (and down) his speech and queer aesthetics. The choice of the timeline is justified, first, by demarcating the post resumption of Brazilian cinema (NAGIB, 2002). Second, the emergence of a more committed national films with various representations of LGBT people (GARCIA, 2012). Third, it is from the year 2002 there is a greater heating of the national documentary production (Maruno, 2008). And fourth, the configuration of the LGBT movement in the last decade, which struggle for media spaces - including the cinema to give social existence to his speeches against hegemonic (SIMÕES, FACHINI, 2009). 19 mapped movies, analysis procedures underlie the prior literature and the analysis method filmic representation of LGBT characters that make up the filmic scenarios. In the end, it was possible to infer that, in general, the mapped films and analyzed share of an organic commitment to represent these subjects differently, developing an alternative and opposed to negative and stereotypical representations speech, humanizing the subjects that were out of a possible "humanity." Representing these oppositions and resistances to the discourses of prejudiced order, the filmic representations advance, at times, for upgrades and (re) signification of a place that would serve only to reinforce a control and exclusion strategy. However, to constantly seek to oppose the discourses of prejudiced order, some of these movies fall into the trap of reframing representations of these people characters in hegemonic terms, valuing speeches and aesthetic sanitized and aseptic rather reinvent and circumvent the very discursive regime which elects and defines how LGBT should behave to achieve a status of "viable life". While others bet on an identity reification and some open onto views of homosexuality, travestilidade, transsexuality or bisexuality as real critical land deconstruction of sex / gender, representing these subjects through ethnic and identity model. However, there are those films that are not just concerned with opposing the stereotyped portraits, to draw up a positive image of LGBT or reduce your creativity to an identity reification. In addition, betting on a resistance representation is also counterproductive contrasexual and queer.